please answer my question
Attachments:
![](https://hi-static.z-dn.net/files/ddb/cc6da8d348a3abca43f3a6ec4b49f25b.jpg)
Answers
Answered by
1
4n^2 + 5n - 636
= 4n^2 - 48n + 53n - 636
= 4n ( n - 12) + 53 (n - 12)
= (n - 12) (4n + 53)
= 4n^2 - 48n + 53n - 636
= 4n ( n - 12) + 53 (n - 12)
= (n - 12) (4n + 53)
vansh6012:
thanks bhai
Answered by
29
4n² + 5n - 636
4n² - 48n + 53n - 636
4n ( n - 12 ) + 53 ( n - 12 )
( n - 12 ) ( 4n + 53 ).
4n² - 48n + 53n - 636
4n ( n - 12 ) + 53 ( n - 12 )
( n - 12 ) ( 4n + 53 ).
Similar questions